St. Thomas' solution of the problem of faith and reason - Melsen, Andrew G. van (Sapientia, 1974)
The purpose of this article is not to discuss in a general way Thomas' solution of the controversy between fideism and rationalism. What we have in mind is a more specific question, namely to what extent this solution is still valid in the light of later developments of scientific thought. For it is obvious that Thomas' solution cannot be separated from the mediaeval conception of science. This question is specially interesting when we think of two historical fats. The first is that there can hardly be any doubt that Thomas' solution has the historical merit of having created room for the cultivation of positive science. Without Thomas' distinction between the realm of faith and that of reason it would have been mucho more difficult for mediaeval thought to acknowledge the real importance of the scientific heritage of ancient culture with which the mediaeval world became acquainted through the Arabs. There is, however, still another fact to consider. When some centuries after Thomas the different medioeval attempts at developing the scientific heritage of Greek-Arabian culture succeeded and a more or less autonomous positive science carne into existence, a serious conflict between reason and faith resulted which, in different forms, lasted till our days. At first, the conflicts were more or less of a factual nature: the new sciencie had conceptions of the universe and of creation which considerably differed from those which were found in the Bible (e. g., Galileo, Darwin) ; later on the conflict shifted to the social order (Marx) , and in our times to the moral order.